2018
DOI: 10.18632/oncotarget.25556
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of two gold(I)-N-heterocyclic carbene complexes in A2780 human ovarian cancer cells: a comparative proteomic study

Abstract: Au(NHC) and Au(NHC)2, i.e. a monocarbene gold(I) complex and the corresponding bis(carbene) complex, are two structurally related compounds, endowed with cytotoxic properties against several cancer cell lines. Herein, we explore the molecular and cellular mechanisms at the basis of their cytotoxicity in A2780 human ovarian cancer cells. Through a comparative proteomic analysis, we demonstrated that the number of modulated proteins is far larger in Au(NHC)2-treated than in Au(NHC)-treated A2780 cells. Both gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 72 publications
4
55
0
Order By: Relevance
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…S84-S103 †). Whereas gold dithiocarbamates are known to react with thiols, 45,49,51,69 detailed studies to unravel the potential mechanism of activity do not exist. HPLC trace of the reaction solution revealed one distinct band at a different retention time (R t -5.00 minutes) from 2a (R t -6.03 minutes) or GSH (R t -1.72 minutes) ( Fig.…”
Section: Reactivity Of Gold(iii) Dithiocarbamates With Cysteine Thiolsmentioning
confidence: 99%
“…Gold-NP, polymer NP or liposomes are also used as carriers of tumour-peptide vaccines that play an important role in tumour immunotherapy [ 2 , 23 , 24 ]. Chemotherapy based on platinum (II), ruthenium and gold (III) compounds also kills tumour cells [ 25 , 26 ]. One of the most studied gold (III) compounds is the anti-rheumatic drug Auranofin as a cancer treatment [ 2 , 27 ].…”
Section: Nanomedicinementioning
confidence: 99%